2014
DOI: 10.1371/journal.pntd.0002904
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset of the Serological Response against the 18 kDa Small Heat Shock Protein of Mycobacterium ulcerans in Children

Abstract: A previous survey for clinical cases of Buruli ulcer (BU) in the Mapé Basin of Cameroon suggested that, compared to older age groups, very young children may be less exposed to Mycobacterium ulcerans. Here we determined serum IgG titres against the 18 kDa small heat shock protein (shsp) of M. ulcerans in 875 individuals living in the BU endemic river basins of the Mapé in Cameroon and the Densu in Ghana. While none of the sera collected from children below the age of four contained significant amounts of 18 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…All of the studied communities along the Offin River basin were designated endemic; the communities included Ntobroso and Achiase in the Atwima district, upstream and midstream of the river, respectively, and Mfantsiman in the Upper Denkyira district, downstream of the river. Extensive seroepidemiological studies (34)(35)(36) conducted in these communities indicated high levels of serological evidence of exposure of community members to M. ulcerans 18-kDa small heat shock protein (hsp) (33), irrespective of the disease burden.…”
Section: Methodsmentioning
confidence: 99%
“…All of the studied communities along the Offin River basin were designated endemic; the communities included Ntobroso and Achiase in the Atwima district, upstream and midstream of the river, respectively, and Mfantsiman in the Upper Denkyira district, downstream of the river. Extensive seroepidemiological studies (34)(35)(36) conducted in these communities indicated high levels of serological evidence of exposure of community members to M. ulcerans 18-kDa small heat shock protein (hsp) (33), irrespective of the disease burden.…”
Section: Methodsmentioning
confidence: 99%
“…In that vein, findings from our seroepidemiological studies, where we determined antibody titers against the 18-kDa-small heat shock protein of M. ulcerans in healthy individuals living in BU endemic areas of Cameroon and Ghana, suggested that children below the age of 5 years are considerably less exposed to the pathogen than older children. This indicates that exposure to M. ulcerans and thus infection with the pathogen might occur outside of the relatively small movement range of very young children and increases in older children with more direct environmental contacts further away from their homes [59]. Hence, in African, BU endemic settings infection through vectors commonly present in the limited movement radius of young children appears unlikely.…”
Section: Potential Vectorsmentioning
confidence: 99%
“…Another intriguing aspect of these seroepidemiological investigations in BU endemic regions is that exposure to M. ulcerans in many cases seems to lead to nonsymptomatic infections [59,60]. Factors accounting for this diverse outcome of infection may be manifold, as observed also for other mycobacterial diseases such as tuberculosis and leprosy.…”
Section: Potential Vectorsmentioning
confidence: 99%
“…90 In line with this observation, sero-epidemiological studies in Ghana and Cameroon have indicated that children below 5 years of age are considerably less exposed to M. ulcerans than older children. 91 Infection by M. ulcerans might thus occur outside the relatively small movement range of very young children. Exposure and the associated risk of developing BU disease appears to increase at an age when the children are having more intense environmental contacts, including direct exposure to water bodies peripheral to their homes.…”
Section: Age and Sexmentioning
confidence: 99%
“…Seroepidemiological studies in Ghana and Cameroon have shown that children are much earlier exposed to malaria parasites than to M. ulcerans, indicating that an involvement of insect vectors commonly found close to the households is highly unlikely. 91 Results of other studies have been compiled in a conceptual model, where M. ulcerans, present in the aquatic environment such as in detritus, mud, or plant biofilms, is concentrated by water-filtering organisms 70,113 and subsequently passed on to predatory aquatic vertebrates and invertebrates feeding on this prey. Infection from potential environmental reservoirs may take place via puncture wounds or lacerations after contact with concentrated M. ulcerans sources or via invertebrate vectors, such as aquatic insects.…”
Section: Hypotheses On the Mode(s) Of M Ulcerans Transmissionmentioning
confidence: 99%